Wife's Self-efficacy when her husband is serving a criminal sentence and its Relevance to Indonesian Family Law: Mubadalah Perspective - Syarpani, Syarpani (SMART: Journal of Sharia, Traditon, and Modernity, 2024)
This article examines the wife's self-efficacy when her husband is serving a criminal sentence and its relevance to family law in Indonesia. The formulation of this research is the wife's self-efficacy in maintaining the household when the husband is serving a sentence in the Lampung Provincial Penitentiary; How is the fulfilment of family maintenance when the husband is serving a sentence in the Lampung Provincial Penitentiary?; and How is the impact on the family when the husband is serving a sentence in the Lampung Provincial Penitentiary and its contribution to the development of family law in Indonesia. The research objectives include the wife's self-efficacy in maintaining the household when the husband is imprisoned in the Lampung Provincial Penitentiary, the fulfilment of family maintenance while the husband is serving a sentence, as well as the impact on the family and its contribution to the development of family law in Indonesia. This research uses a qualitative approach with field research conducted in several correctional institutions and religious courts in Lampung Province. Data were obtained from primary and secondary sources, analysed with qualitative methods using mubadalah theory. The results showed that wives facing this situation experienced significant economic, social, physical, and mental impacts, yet they were able to adapt to the conditions. Wives' self-efficacy, which reflects awareness of marital partnership, is key in maintaining family integrity, with mubadalah relationship patterns as a strategy to maintain household harmony in the face of trials such as husbands who become prisoners.